IFPRI Egypt-AUC: Launch of IFPRI's GFPR 2018 - Fan, Shenggen; Breisinger, Clemens (2018)
As part of the IIFPRI Egypt Seminar in partnership with AUC Economics Department | "THE LAUNCH OF IFPRI’s GLOBAL FOOD POLICY REPORT: “Reaping the benefits and facing the challenges of globalization in Egypt"